Patterns, Correlates and Knowledge of Health Implications Associated with Alcohol Consumption: A Mix-Method Approach - Oyebode, Abiodun Oluwaseun; Bankole, Taofik Olatunji (International Journal of Medical and Health Sciences Research, 2019)
Heavy consumers of alcohol are more likely to indulge in social vices due to cognitive impairment and students who engage in high alcohol intake are more likely to perform poorly in their academics. This study describes the patterns of alcohol consumption and investigated the correlates of and knowledge of health implications related with alcohol consumption in the studied locations. This study was a cross sectional research design and employed the mix-research methods. The quantitative data was generated through a survey with 400 respondents selected through a proportionate sampling design from Kwara State College of Education, University of Ilorin, and Federal Polytechnic, Offa. The qualitative evidence was captured through 10 in-depth interviews using a snowball sampling technique to recruit students who are heavy consumers of alcohol. The quantitative data was analysed using Stata version 14. The chi-square and multiple regression analysis results showed that amount of alcohol consumed and perception of were significantly associated with students’ knowledge of health implications associated with alcohol consumption (p<0.05). Results of the multiple regression showed that students’ knowledge on health implications associated with alcohol consumption contributed about 10% to amount of alcohol consumed and their perception of alcohol consumption. Results of the qualitative study revealed that students were of the view that moderate consumption of alcohol was needful with no negative health implications arising from it. The study concluded that students’ perception of the health implications related with consumption of alcohol influenced amount of alcohol and measures taken to reduce quantity of alcohol consumed.